Cooking at home to retain nutritional quality and minimise nutrient losses: A focus on vegetables, potatoes and pulses. Issue 4 (26th October 2022) - Coe, Sarah; Spiro, Ayela
Abstract: Cooking at home has experienced a decline in many countries since the mid‐20th century. As rates of obesity have increased, there has been an emphasis on more frequent home cooking, including its incorporation into several food‐based dietary guidelines around the world as a strategy to improve dietary quality. With the recent trend towards the adoption of diets richer in plant‐based foods, many consumers cooking at home may now be cooking plant foods such as vegetables, potatoes and pulses more often. It is, therefore, timely to explore the impact that different home cooking methods have on the range of nutrients (e.g. vitamin C and folate) and bioactive phytochemicals (e.g. carotenoids and polyphenols) that such plant foods provide, and this paper will explore this and whether advice can be tailored to minimise such losses. The impact of cooking on nutritional quality can be both desirable and/or undesirable and can vary according to the cooking method and the nutrient or phytochemical of interest. Cooking methods that expose plant foods to high temperatures and/or water for long periods of time (e.g. boiling) may be the most detrimental to nutrient content, whereas other cooking methods such as steaming or microwaving may help to retain nutrients, particularly those that are water‐soluble. Dishes that use cooking liquids may retain nutrients that would have been lost through leaching. It may be helpful to provide the public with more information about better methods to prepare and cook plant foods to minimise any nutrient losses. However, for some nutrients/phytochemicals the insufficient and inconsistent research findings make clear messages around the optimal cooking method difficult, and factors such as bioaccessibility rather than just quantity may also be important to consider.